2017
DOI: 10.1007/s00062-017-0639-z
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Vessel Dissection in Endovascular Treatment of Acute Ischemic Stroke

Abstract: Purpose Knowledge about the localization and outcome of iatrogenic dissection (ID) during endovascular treatment of acute ischemic stroke (AIS) is limited. We aimed to determine the frequency, clinical aspects and morphology of ID in endovascular AIS treatment and to identify predictors of this complication. Methods Digital subtraction angiography (DSA) of ID carried out during endovascular treatment between January 2000 and March 2012 have been re-evaluated. The ID localization and morphology were analyzed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
6
23
0
Order By: Relevance
“…The rate of complications in patients with NIHSS < 8 was comparable to recent meta-analysis data [20] and matches the frequency of complications observed in patients presenting with NIHSS ≥ 8 in this registry. Two-thirds of complications were comprised by iatrogenic cervical dissections and periprocedural vasospasms, both associated with relatively low risk of prompting unfavorable outcomes [21]. When adjusting for the lower rates of successful reperfusion in patients with procedural complications, we did not observe an independent effect of complications on outcome (data not shown).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The rate of complications in patients with NIHSS < 8 was comparable to recent meta-analysis data [20] and matches the frequency of complications observed in patients presenting with NIHSS ≥ 8 in this registry. Two-thirds of complications were comprised by iatrogenic cervical dissections and periprocedural vasospasms, both associated with relatively low risk of prompting unfavorable outcomes [21]. When adjusting for the lower rates of successful reperfusion in patients with procedural complications, we did not observe an independent effect of complications on outcome (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…While a proportion of patients will most likely benefit from routine EVT by preventing infarct growth, EVT also harbors the risk of worsening cerebral perfusion by thrombus dislocation and subsequent collateral shutdown and other procedural complications [20] (e.g. dissection [21], perforation [22], infarct to new territory [23], etc. ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that iatrogenic vessel dissection occurs in 0.6%-3.9% of mechanical thrombectomy cases [11] , [12] , [13] . Among these cases, extracranial dissection was more common, whereas intracranial vessel dissection was precisely described in only a small number [11 , 17] . Among approximately 250 cases of mechanical thrombectomy at our institute over the past 5 years, only these 2 patients were definitively diagnosed with iatrogenic intracranial dissection (0.8%) [20] , [21] , [22] , [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, dissection occurred at the initially nonoccluded but mildly arteriosclerotic M1, where a large-bore aspiration catheter shifted up into the distal vessel through the atherosclerotic lesion. Among the few previous reports of intracranial vessel dissection during mechanical thrombectomy, the aspiration catheter was reported as the estimated cause of dissection [17] . Various large-bore aspiration catheters for mechanical thrombectomy have been developed and are now widely used with contact aspiration or an SR and aspiration catheter combined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation